Meropenem dosing recommendations for critically ill patients receiving continuous renal replacement therapy - Weerachai Chaijamorn (2020)
© 2020 Elsevier Inc. Purposes: To gather available meropenem pharmacokinetics and define drug dosing regimens for Asian critically ill patients receiving CRRT. Methods: All necessary pharmacokinetic and pharmacodynamic data from Asian population were gathered to develop mathematic models with first order elimination. Meropenem concentration-time profiles were calculated to evaluate efficacy based on the probability of target attainment (PTA) of 40%fT>4MIC. A group of 5000 virtual patients was created and tested using Monte Carlo simulations for each dose in the models. The optimal dosing regimens were defined as the doses achieved at least 90% of the PTA. Results: The recommended meropenem dosing regimen for Asian critically ill patients receiving CRRT with standard (20–25 mL/kg/h) and high (35 mL/kg/h) effluent rates was 750 mg q 8 h to manage Gram negative infections with expected MIC < 2 mg/L in virtual Asian patients. Some meropenem dosages from available clinical resources could not achieve the aforementioned target. The volume of distribution, body weights and nonrenal clearance significantly contributed to drug dosing adaptation especially in the specific population. Conclusions: A meropenem regimen of 750 mg q 8 h was recommended for Asian critically ill patients receiving 2 different CRRT modalities with standard and high effluent rates. Clinical validation of these results is needed.